2018
DOI: 10.1021/acs.cgd.8b01064
|View full text |Cite
|
Sign up to set email alerts
|

Playing with Isomerism: Cocrystallization of Isomeric N-Salicylideneaminopyridines with Perfluorinated Compounds as Halogen Bond Donors and Its Impact on Photochromism

Abstract: In N-salicylideneaniline derivatives, photochromism occurs by a two-step isomerization mechanism. Photochromism has been reported to be closely related to the molecular conformation of the N-salicylideneanilines (described by the dihedral angle Φ) and to the free available space (V free ) in the crystal. In this contribution, we focus on cocrystals of isomeric Nsalicylideneaminopyridines with perfluorinated halogen bond donors as coformers. The advantage of working with isomers is that they have a similar (if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 76 publications
0
27
0
Order By: Relevance
“…At the same time, it was demonstrated that C=O and C-Br groups compete with each other for the most acidic hydrogen atoms, thus that FIM predictions of synthons based on C-H...Br bonding became less reliable at the presence of C-H...O=C bonding [257]. At the absence of carbonyl groups the FIMs for the N-salicilidenanylines probed with C-I and C-F groups successfully predict all of the C-I...N and many of the C-F...H-C interactions in co-crystals of N-salicilidenanylines with perhalogenated co-formers [259]. Mugheirbi and Tajber analyzed the FIM hotspots around the itraconazole molecule to understand the molecular environment in the mesophase [260].…”
Section: Full Interaction Mapsmentioning
confidence: 97%
“…At the same time, it was demonstrated that C=O and C-Br groups compete with each other for the most acidic hydrogen atoms, thus that FIM predictions of synthons based on C-H...Br bonding became less reliable at the presence of C-H...O=C bonding [257]. At the absence of carbonyl groups the FIMs for the N-salicilidenanylines probed with C-I and C-F groups successfully predict all of the C-I...N and many of the C-F...H-C interactions in co-crystals of N-salicilidenanylines with perhalogenated co-formers [259]. Mugheirbi and Tajber analyzed the FIM hotspots around the itraconazole molecule to understand the molecular environment in the mesophase [260].…”
Section: Full Interaction Mapsmentioning
confidence: 97%
“…This has led to the question of whether the halogen bond-an interaction in many ways similar to hydrogen bond [27][28][29][30]-can have a similar effect on the intramolecular hydrogen transfer and stabilization of the keto-amino tautomer. Unfortunately, despite the research on halogen bonded o-hydroxyimine systems performed to date [31][32][33][34][35][36][37], the answer to this question remained inconclusive. The possible reason for this is that the stabilizing effect of the halogen bond might be too subtle to noticeably affect proton transfer through the highly asymmetric O-H•••N hydrogen bond.…”
Section: Introductionmentioning
confidence: 99%
“…As part of our interest in photo-and thermochromic cocrystals (Carletta et al, 2015(Carletta et al, , 2016(Carletta et al, , 2018, the investigation of compounds analogous to the already studied N-salicylideneaniline derivatives of o-vanillin could lead to a better understanding of the factors influencing photo-and thermochromic behaviour. Indeed, the impact of the intramolecular hydrogen bond with regard to external stimuli (temperature and light) should affect the properties of new analogues.…”
Section: Introductionmentioning
confidence: 99%